Concepts, protocol, variations and current trends in surgery first orthognathic approach: a literature review - Mahmood,Hafiz Taha (2018)
ABSTRACT In the current era of expedited orthodontics, among many clinicians, tertiary care hospitals and patients, surgery first orthognathic approach (SFOA) has gained popularity. The advantages of SFOA (face first approach) are the reduced overall treatment duration and the early improvement in facial esthetics. In SFOA, the absence of a presurgical phase allows surgery to be performed first, followed by comprehensive orthodontic treatment to achieve the desired occlusion. The basic concepts of surgery early, surgery last, SFOA and Sendai SFOA technique along with its variations are reviewed in the present article. The recent advancement in SFOA in the context of preoperative preparation, surgical procedures and post-surgical orthodontics with pertinent literature survey are also discussed.